Avaliação no HAREM: Métodos e medidas - Santos, Diana (2006)
Made available in DSpace on 2009-11-03T15:07:49Z (GMT). No. of bitstreams: 2 06-17.pdf: 973 bytes, checksum: 3395b9b7b53d2796c45aa1fc17edc792 (MD5) SantosCardosoSecoMedidas2006.pdf: 276360 bytes, checksum: bec34f45ea21a31f74076fbe147ceff9 (MD5) Previous issue date: 2006